Composition and taste of beef, pork, and duck meat and bioregulatory functions of imidazole dipeptides in meat - Katsuko Kajiya; Madoka Arino; Akari Koshio; Yuji Minami (Scientific Reports, 2023)
Abstract This study quantified the nutritional components and imidazole dipeptide levels of commercially available meats (beef, pork, and duck), and their effects on taste were quantified via taste recognition devices. Although meat and its products are considered high-risk diets, meat components, such as imidazole dipeptides, exert bioregulatory functions. Further, considering their bioregulatory function, commercial meats’ antioxidant activity and vascular endothelial function were examined. Characteristic variations in nutritional components were observed depending on the type and part of meat analyzed. These components affected the taste and texture of meat. The main imidazole dipeptides detected were anserine (duck meat) and carnosine (beef and pork). Meat with larger quantities of total imidazole dipeptide demonstrated better sensory test results. Therefore, anserine and carnosine effects on taste were determined using a taste recognition device; carnosine alone produced a noticeably bitter taste, whereas adding anserine reduced bitterness and enhanced umami taste. In a few cases, cooking enhanced the quantity of carnosine and/or anserine and their antioxidant activities. We demonstrated the ability of imidazole dipeptides, particularly anserine, to improve nitric oxide production in vascular endothelial cells. This study provides essential information for health-conscious consumers to develop high-quality, functional meat products.